(untitled) (Journal of Economic Research & Business Administration, 2016)
In article questions of management of urban agglomeration are investigated. The author considers that the management has to be based on the accounting of interests of all inhabitants of agglomeration, as living in the center, an agglomeration kernel, and living in settlements – satellites. Harmonization of interests of the population of urban agglomeration has to become a strategic problem of all region. Different difficult system of relationship (economic, social and so forth) demands special methodology of realization of strategic objectives and the solution of tactical tasks. According to the author the economic growth of the region and urban agglomeration is possible at the solution of such problems of public administration, as creating favorable conditions for development of business in the region and urban agglomeration. In article basic qualitative parameters of expensive and resultant elements of efficiency of urban agglomeration are called. The author offers criteria of an assessment of efficiency of strategy of development of urban agglomeration, the approximate list of tools of economic policy of urban agglomeration. Proceeding from orientation to object of management gives typology of economic policy of urban agglomeration.